Diversity of Anaplasma and novel Bartonella species in Lipoptena fortisetosa collected from captive Eld’s deer in Thailand - Wechtaisong, Wittawat; Sri-in, Chalida; Thongmeesee, Kritsada; Yurayart, Nichapat; Akarapas, Chatlada; Rittisornthanoo, Ganyawee; Bunphungbaramee, Natcha; Sipraya, Natthanicha; Bartholomay, Lyric C.; Maikaew, Umaporn; Kongmakee, Piyaporn; Saedan, Arpussara; et al. (Frontiers in Veterinary Science, 2023)
Lipoptena insects are important ectoparasites of cervids and may affect humans that are incidentally bitten. The presence of zoonotic pathogen DNA, such as Anaplasma, and Bartonella, raises the importance of Lipoptena insects in veterinary and human medicine. Eld’s deer (Rucervus eldii thamin), an endangered wild ruminant in Thailand, are bred and raised in the open zoo. The semi-wild zoo environment suggests ectoparasite infestation and potential risk for mechanical transmission of pathogens to visitors, zoo workers, or other animals. However, epidemiology knowledge of pathogens related to endangered wild ruminants in Thailand is limited. This study aims to determine the prevalence and diversity of Anaplasma and Bartonella in the L. fortisetosa collected from captive Eld’s deer in Chon Buri, Thailand. Of the 91 Lipoptena DNA samples obtained, 42 (46.15%) and 25 (27.47%) were positive for Anaplasma and Bartonella by molecular detection, respectively. Further, 42 sequences of Anaplasma (4 nucleotide sequence types) showed 100% identity to those detected in other ruminants and blood-sucking ectoparasites. Twenty-five sequences of Bartonella (8 nucleotide sequence types) showed 97.35%–99.11% identity to the novel Bartonella species from sika deer and keds in Japan. Phylogenetic trees revealed Anaplasma sequences were grouped with the clusters of A. bovis and other ruminant-related Anaplasma, while Bartonella sequences were clustered with the novel Bartonella species lineages C, D, and E, which originated from Japan. Interestingly, a new independent lineage of novel Bartonella species was found in obtained specimens. We report the first molecular detection of Anaplasma and Bartonella on L. fortisetosa, which could represent infectious status of captive Eld’s deer in the zoo. Wild animals act as reservoirs for many pathogens, thus preventive measures in surrounding areas should be considered to prevent pathogen infection among animals or potential zoonotic infection among humans.